Foreign Direct Investment and Exports: Complementarity or Substitutability An Empirical Investigation - Bouras, Hela; Raggad, Bechir (International Journal of Economics and Financial Issues, 2015)
The relationship between trade and direct investment, which is one of the main features of globalization, is complex and cannot be deducted from a purely theoretical analysis. The present paper seeks to lay the analytical foundation that would define the nature of the relationship – be it complementary or substitutive - between Exports and Foreign Direct Investment (FDI). The purpose of our use of disaggregate sectoral database is to explore these issues econometrically while analyzing and decomposing the nature of the relationship between FDI and exports. The estimation results showed a complementary effect or a ripple effect between Exports and FDI at the macro level for both manufactured and non-manufacturing sectors. Our findings have also been supported by predominant literature which finds positive relationships between FDI and exports. Keywords: FDI; Exports; Substitutability; Complementarity; manufacturing; non-manufacturing. JEL Classifications: F02; F4; F14